THE ACADEMICAL SPORT AND THE STRATEGIES OF PERMANENCE IN THE UNIVERSITY: THE BLACK PLAYERS (Fiep Bulletin - online, 2014)
The relationship between sport and education in Brazil, is still incipient, we don't have a road or a relationship as clear as observed, for instance, in the north academical sport American. However, in any way, we can say that in Brazil, we have cases in that, the academical sport is used by black players as permanence strategy in the higher education. This permanence and in some cases access, it can be reached by the obtaining of bags for the players (bag feeding, bag lodging, discount bag in the monthly fee, etc). To contemplate on such a theme we observed two situations the first is related the Academical League Viçosense belonging to the Federal University of Lush, and Monday, it is seen in some private universities that offer bags for players.
Keywords: sociology of the sport; black; academical sport